2002
DOI: 10.1021/jo026322y
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Epoxidation of Alkenes Catalyzed by 2-Fluoro-N-Carbethoxytropinone and Related Tropinone Derivatives

Abstract: Several alpha-substituted N-carbethoxytropinones have been evaluated as catalysts for asymmetric epoxidation of alkenes with Oxone, via a dioxirane intermediate. alpha-Fluoro-N-carbethoxytropinone (2) has been studied in detail and is an efficient catalyst which does not suffer from Baeyer-Villiger decomposition and can be used in relatively low loadings. This ketone was prepared in enantiomerically pure form using chiral base desymmetrization of N-carbethoxytropinone. Asymmetric epoxidation catalyzed by 2 aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(26 citation statements)
references
References 40 publications
1
23
0
2
Order By: Relevance
“…This example is nonetheless instructive since it demonstrates that a seemingly innocent H → F substitution likely disfavors the proposed spiro-transition state that underpins selectivity . Seminal studies by Armstrong , and Denmark , have validated fluorinated tropinone scaffolds as efficient catalysts for the stereoselective epoxidation of alkenes. Selectivities derive from the rigid alkaloid framework in which the amine moiety inhibits alkene approach to the top face of the transient dioxirane generated upon oxidation.…”
Section: C­(sp3)–f Centers In Cyclic Scaffoldsmentioning
confidence: 99%
“…This example is nonetheless instructive since it demonstrates that a seemingly innocent H → F substitution likely disfavors the proposed spiro-transition state that underpins selectivity . Seminal studies by Armstrong , and Denmark , have validated fluorinated tropinone scaffolds as efficient catalysts for the stereoselective epoxidation of alkenes. Selectivities derive from the rigid alkaloid framework in which the amine moiety inhibits alkene approach to the top face of the transient dioxirane generated upon oxidation.…”
Section: C­(sp3)–f Centers In Cyclic Scaffoldsmentioning
confidence: 99%
“…A significant activating effect by a-fluorine substitution has been observed [2][3][4][5] and then extensively studied [6][7][8][9][10][11][12][13][14][15]. We have recently shown that, during epoxidation of methyl p-methoxycinnamate (Scheme 1), enantiopure tri-substituted cyclohexanones 1-3 were more efficient, leading to higher ee% and higher yields, when the halogen was axial (1a-3a) than when the halogen was equatorial (1e-3e) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Katalysatoren auf Basis chiraler Ketone für die asymmetrische Epoxidierung kçnnen weitgehend in drei Typen unterteilt werden (Schema 11): 1) C 2 -symmetrische Kataly-satoren; [26] 2) bicyclische Katalysatoren [27] und 3) von Kohlenhydraten abgeleitete Katalysatoren. [28] Es wurde eine umfassende Übersicht zu den Entwicklungen der veranschaulichten Katalysatortypen bis 2007 und ihrer Rolle in enantioselektiven Epoxidierungen verçffentlicht.…”
Section: Verfahren Zur Epoxidierung Von Nichtaktivierten Alkenen Und unclassified
“…[29] 26,29,30] Der von Fructose abgeleitete Katalysator 42 (Schema 12) war einer der ersten Katalysatoren für die hochenantioselektive Epoxidierung. [31] (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Mol-%) und eine geringere Aufgabe von Oxone (1.5 ¾quiv.) ermçglichte und zu hçheren Umwandlungen führte.…”
Section: Verfahren Zur Epoxidierung Von Nichtaktivierten Alkenen Und unclassified